Zingela (Asparagaceae, Scilloideae), a distinct new urgineoid genus from KwaZulu-Natal, South Africa - Crouch, Neil R.; Martínez-Azorín, Mario; Crespo, Manuel B.; Pinter, Michael; Alonso-Vargas, María Á. (Phytotaxa, 2018)
In the course of resolving the identity of plants usually named ‘Drimia indica’ from KwaZulu-Natal Province, South Africa, molecular and morphological data revealed the identity of more than one taxon carrying this name. Our studies support the establishment of a new urgineoid genus, Zingela gen. nov., to accommodate a species (Z. pooleyorum) collected and illustrated some 50 years ago, but never validly published. We here provide data on its morphology, ecology, and distribution.